Donald MacJannet and Anita and Woody Woodworth with Elms School staff members and students during a trip to northern Africa, 1927 - Richardet, Jean (Tufts Archival Research Center, 2005)
4x9; taken from MS024/007-104#006 - "MacJannet School photos, ca. 1930"